(x2−1x2)2\left(\frac{x^{2}-1}{x^{2}}\right)^{2}(x2x2−1)2
asked by guest on Mar 25, 2025 at 1:31 am
You asked:
MathBot Answer:
(x2−1x2)2=(x2−1)2x4\displaystyle {\left( \frac{{x}^{2} - 1}{{x}^{2}} \right)}^{2} = \frac{\left(x^{2} - 1\right)^{2}}{x^{4}} (x2x2−1)2=x4(x2−1)2
(x2−1x2)2=1−2x2+1x4{\left( \frac{{x}^{2} - 1}{{x}^{2}} \right)}^{2} = 1 - \frac{2}{x^{2}} + \frac{1}{x^{4}}(x2x2−1)2=1−x22+x41
(x2−1x2)2=(x−1)2(x+1)2x4{\left( \frac{{x}^{2} - 1}{{x}^{2}} \right)}^{2} = \frac{\left(x - 1\right)^{2} \left(x + 1\right)^{2}}{x^{4}}(x2x2−1)2=x4(x−1)2(x+1)2